Protections and Social Support of Exclusive Breastfeeding for Mothers with COVID-19: Message for Health Promotion during The Pandemic - Khairunnisaa, Khairunnisaa; Ayubi, Dian (Pediomaternal Nursing Journal, 2022)
Introduction: The COVID-19 pandemic is a concern regarding the potential failure of exclusive breastfeeding in mothers with COVID-19. This study reviews previous research describing the protective and social support practices of exclusive breastfeeding in mothers with COVID-19.Methods: A systematic search was conducted in March-June 2021 using databases such as Scopus and PubMed with a deadline of 2020-2021 that met the inclusion criteria. 462 articles which were then entered in the elimination stage until the final 16 articles were eligible for a full text review. Study quality was assessed using the Newcastle-Ottawa Scale (NOS).Results: We identified 16 studies reporting 1,865 cases of maternal infection with COVID-19. An overview of breastfeeding protection practices is carried out through rooming-in and post-delivery skin contact. This practice includes implementing strict precautions such as wearing a mask, social distancing, and maintaining hand and breast hygiene. All babies born to mothers who practice breastfeeding protection are not infected with COVID-19. Social support from health workers, families and health care management cannot be overlooked in ensuring breastfeeding continues and precautions are followed. Conclusion: In mothers with COVID-19 breastfeeding is still recommended but must be supported by strict health protocols. Social support cannot be neglected to protect exclusive breastfeeding practices and ensure that COVID-19 precautions are adhered to.